Family Health Profile Index in the Village of Ndoru Rea I - Yustina PM Paschalia; Irwan Budiana (Science Midwifery, 2022)
Background: The challenge of health development in achieving the highest public health requires a family approach which is initiated by mapping the problems in depth from the life cycle approach through home visits. Objective: This study aims to determine the index of family health profiles in Ndoru Rea I Village. Methods: This research is a descriptive research with a survey approach to describe the family health index. The population in this study were all families in the Ndoru Rea I Village area, totaling 237 families with a total sample of the population. Data analysis was carried out descriptively and presented in the form of tables and narratives. Results: The coverage of each indicator of a healthy family is that families participate in the family planning program 34.29%, mothers give birth in health facilities 84,62% of infants receive complete basic immunizations 100%, infants are exclusively breastfed for 6 months 100%, growth of toddlers is monitored every year. month 91.80%, patients with pulmonary tuberculosis were treated according to the standard 100%, patients with hypertension had regular treatment 27.27%, patients with severe mental disorders were not neglected 0%, no family members smoked 41.77%, families had access to/used water clean 95.78%, families have access to / use healthy latrines 93.25%, families are already members of National health insurance 34.18%. Conclusion: Ndoru Rea 1 Village is included in the unhealthy village category, where the Healthy Family Index (IKS) of Ndoru Rea 1 Village is 0.177